2011
DOI: 10.1007/s11136-011-9934-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Distress Thermometer to discern clinically relevant quality of life differences in women with breast cancer

Abstract: Moderately to severely distressed patients have significantly lower QOL than those with expected or mild distress. The DT provides a quick and easy screening tool to alert the healthcare team to clinically relevant alterations in patients' QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 47 publications
5
28
1
Order By: Relevance
“…Finally, the distress thermometer is primarily a distress screening instrument. Although recent work in breast cancer has shown that moderately to severely distressed patients have significantly lower quality of life than those with mild distress and that the distress thermometer provides a quick and easy screening tool to alert the healthcare team to clinically relevant alterations in patients' quality of life [39], this has not yet been demonstrated in caregivers or in the context of HNC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the distress thermometer is primarily a distress screening instrument. Although recent work in breast cancer has shown that moderately to severely distressed patients have significantly lower quality of life than those with mild distress and that the distress thermometer provides a quick and easy screening tool to alert the healthcare team to clinically relevant alterations in patients' quality of life [39], this has not yet been demonstrated in caregivers or in the context of HNC.…”
Section: Discussionmentioning
confidence: 99%
“…Distress is prevalent in women with breast cancer, with reports of multiple physical, psychological, and social needs and a trajectory of worry, stress, and loss (Head et al, 2012). Newly diagnosed patients with breast cancer (stages I–IV) reported a mean distress score of 4.87 (SD = 3.2) (Head et al, 2012); a score of 4 or more indicates moderate to severe distress (National Comprehensive Cancer Network [NCCN], 2014). Distress screening can be difficult to integrate into routine care (Holland, Kelly, & Weinberger, 2010).…”
mentioning
confidence: 99%
“…The DT is used to measure psychosocial distress and related problems in cancer patients (see Appendix 1). The National Comprehensive Cancer Network (NCCN) developed the DT and it is an important part of the routine cancer care recommended in their good practice guidelines [21,25,26]. Permission was given by the NCCN for the use of the DT tool in this research project.…”
Section: Distress Thermometermentioning
confidence: 99%
“…This involved suggesting to the Clicker to contact their treating medical practitioner for assistance and referral to an appropriate health care practitioner as necessary. A score of less than four indicated mild distress or 'expected distress' that could be investigated and managed by the SBCN or the breast cancer team [21]. The DT score of four was chosen because this score was used in a community-based telephone helpline for cancer patients and their careers, which is similar to online contact in that the assessor and the patient are not meeting face-to-face [26].…”
Section: Distress Thermometermentioning
confidence: 99%
See 1 more Smart Citation